Peran Dimensi Mentoring dalam Upaya Peningkatan Kualitas Sumber Daya Manusia - Martoredjo, Nikodemus Thomas (Bina Nusantara University, 2015)
This article discusses the development of human resources within an organization or company. One approach that can be done to improve the quality of human resources is mentoring activities. By using library study method, research found that mentoring activities give a positive impact not only for the mentee but also for the mentor and can improve performance of the organization or company. Thus mentoring with a variety of models can be used effectively for the development of human resources in order to support the organization to be more competitive and to face the globalization. Although there are challenges in implementing mentoring activities, with good planning and regular evaluation, maximum results can be achieved.